2019
DOI: 10.1186/s12935-019-1076-7
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Degradation of long non-coding RNA-CIR decelerates proliferation, invasion and migration, but promotes apoptosis of osteosarcoma cells

Abstract: BackgroundOver the years, long non-coding RNAs (lncRNAs) have been clarified in malignancies, this research was focused on the role of lncRNA cartilage injury-related (lncRNA-CIR) in osteosarcoma cells.MethodsLncRNA-CIR expression in osteosarcoma tissues and cells, and adjacent normal tissues and normal osteoblasts was determined, then the relations between lncRNA-CIR expression and the clinicopathological features, and between lncRNA-CIR expression and the prognosis of osteosarcoma patients were analyzed. Mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…For example, downregulation of NCK-AS1 modulates cell resistance to cisplatin in OS (Cheng et al, 2019). LncRNA-CIR accelerates OS cell proliferation and represses cell apoptosis (Liu et al, 2019). Moreover, HIF-1α induced lncRNA FOXD2-AS1 could promote OS progression by repressing the expression of p21 (Ren et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…For example, downregulation of NCK-AS1 modulates cell resistance to cisplatin in OS (Cheng et al, 2019). LncRNA-CIR accelerates OS cell proliferation and represses cell apoptosis (Liu et al, 2019). Moreover, HIF-1α induced lncRNA FOXD2-AS1 could promote OS progression by repressing the expression of p21 (Ren et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, RRM2 is involved in miR-520a-mediated inactivation of the Wnt/β-catenin pathway during the development of non-small cell lung cancer [ 37 ]. RRM2 silencing has been suggested to inactivate the Wnt/β-catenin signaling pathway by increasing GSK-3β phosphorylation in multiple myeloma [ 38 ]. Our hypothesis that there is an interplay between miR-582-3p and RRM2 was confirmed by our findings, which demonstrated that miR-582-3p suppresses RRM2 expression to attenuate its carcinogenic effects.…”
Section: Discussionmentioning
confidence: 99%
“…lncRNAs play a crucial role in multiple processes that modulate gene expression, and their transcription can lead to gene silencing or gene activation [ 29 , 30 ]. It has been revealed that lncRNAs participate in the biological processes of many diseases, including cancer, regulating cell proliferation, apoptosis, differentiation, and metastasis [ 31 , 32 ]. For example, elevated levels of lncRNA ROR in PCa tissue are associated with late tumor staging, lymph node or distant metastasis, and modulation of the AKT pathway to promote malignant proliferation of PCa cells [ 33 ].…”
Section: Discussionmentioning
confidence: 99%